2019
DOI: 10.3727/108354219x15458295631891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Airbnb on Customers' Behavior In the UK Hotel Industry

Abstract: The sharing economy is nowadays disrupting the hotel industry. Airbnb is one of the best examples of such an issue. In order to find approaches for hotels to mitigate the threat from these new accommodation forms, the present article focuses on the major elements influencing customers to choose this new platform and other related aspects affecting the future of the hotel industry. Previous studies have looked at how Airbnb influences customer behavior, but this is one of the first studies dealing with an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…While Airbnb hosts derive economic and social benefits by renting their idle spaces to guests (Alrawadieh and Alrawadieh, 2018), traditional hotels may lose revenue because of Airbnb’s increasing competition (Guttentag and Smith, 2017; Zervas et al , 2017; Benítez-Aurioles, 2019). Airbnb has several key strengths including economic value and the opportunity for more authentic local experiences (Guttentag, 2015; Guttentag et al , 2018; Lin et al , 2019; Lu and Tabari, 2019). Indeed, numerous studies into Airbnb guest motivations have highlighted the particular importance of economic value as a motivator for Airbnb stays (Guttentag et al , 2018; Sthapit and Jiménez-Barreto, 2018; Tussyadiah, 2015; Tussyadiah and Pesonen, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While Airbnb hosts derive economic and social benefits by renting their idle spaces to guests (Alrawadieh and Alrawadieh, 2018), traditional hotels may lose revenue because of Airbnb’s increasing competition (Guttentag and Smith, 2017; Zervas et al , 2017; Benítez-Aurioles, 2019). Airbnb has several key strengths including economic value and the opportunity for more authentic local experiences (Guttentag, 2015; Guttentag et al , 2018; Lin et al , 2019; Lu and Tabari, 2019). Indeed, numerous studies into Airbnb guest motivations have highlighted the particular importance of economic value as a motivator for Airbnb stays (Guttentag et al , 2018; Sthapit and Jiménez-Barreto, 2018; Tussyadiah, 2015; Tussyadiah and Pesonen, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Mody et al (2017) surveyed Airbnb and hotel guests and found that the former were more likely to have had experiences relating to all of the experiential dimensions measured (entertainment, education, escapism, esthetics, serendipity, localness, communities and personalization). For Airbnb guests, these various benefits apparently outweigh the potential drawbacks of Airbnb stays, which may include lack of privacy, safety issues and/or unfamiliarity with sharing platforms (Sedlacek, 2016; Tussyadiah and Pesonen, 2018; Poon and Huang, 2017; Lu and Tabari, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, Airbnb stimulates locals to become more entrepreneurial by putting fraction of their property available for the lodging of tourists and by the creation of additional jobs, such as maintenance, renovation of property, etc. (Lu & Tabari, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review and analysis reveal an array of factors that are influencing attitude, behavioural intentions or actual behaviour of individuals in the sharing economy context. Primarily, studies consider economic advantages as a dominant factor which drives consumers to choose sharing economy offerings (Amirkiaee & Evangelopoulos, 2018;Godelnik, 2017;Hallem et al, 2019;Lu & Tabari, 2019;Pappas, 2017;Tran & Filimonau, 2020). However, Hamari et al (2016) and Laurenti & Acuña (2020) pointed out opposite claims.…”
Section: Factors Influencing Sharing Economy Participationmentioning
confidence: 99%